2021
DOI: 10.1039/d1tc01034d
|View full text |Cite
|
Sign up to set email alerts
|

Topological quantum phase transition in the magnetic semimetal HoSb

Abstract: Magnetic topological semimetals, a novel state of quantum matter with nontrivial band topology, have emerged as a new frontier in physics and materials science. An external stimulus like temperature or...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…3 a,b) yielded and , for HoBi and DyBi, respectively. Similarly, it has recently been shown that Kohler’s scaling is effective at K in HoSb and ErBi 25 , 45 . For other REPn containing magnetic RE , Kohler’s rule was disobeyed in the entire covered range of temperature 12 , 27 , 34 .…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…3 a,b) yielded and , for HoBi and DyBi, respectively. Similarly, it has recently been shown that Kohler’s scaling is effective at K in HoSb and ErBi 25 , 45 . For other REPn containing magnetic RE , Kohler’s rule was disobeyed in the entire covered range of temperature 12 , 27 , 34 .…”
Section: Resultsmentioning
confidence: 77%
“…The presence of a rare-earth element with partially filled f -shells in REPn compounds provides even more fascinating physical properties. PrBi has been reported to exhibit nontrivial Berry phase and quadrupolar moment 24 , whereas topological quantum phase transition has been proposed in HoSb 25 . Several antiferromagnets among REPn family have been reported to demonstrate XMR 12 , 15 , 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…And under strong spin–orbit coupling (SOC), the electron spins and crystal momentum are locked together, forming a helical spin texture in the momentum space of the surface states of TIs. 46,63,66–72 Fig. 6 shows the surface state and Fermi surface (FS) in the (001) plane for the AEIn 2 As 2 system at atmospheric pressure and induced zero band gap pressure.…”
Section: Resultsmentioning
confidence: 99%
“…And under strong spin-orbit coupling (SOC), the electron spins and crystal momentum are locked together, forming a helical spin texture in the momentum space of the surface states of TIs. 46,63,[66][67][68][69][70][71][72] To confirm that the effect of stress drives the topological phase transition of the AEIn 2 As 2 systems, we calculated the Wannier Charge Center (WCC), as shown in Fig. 7.…”
Section: Topological Quantum Phase Transitionmentioning
confidence: 99%
“…To eliminate the pollution of antibiotics to the environment, researchers in various countries have adopted a variety of means to degrade antibiotics and other pollutants, including adsorption, membrane separation, biodegradation, photocatalysis, electrocatalysis, thermocatalysis, piezoelectric catalysis, ultrasonic catalysis, and so on. [ 6–16 ] Among these technologies, photocatalysis is a green technology that degrades antibiotics with the help of sunlight, which has been favored by researchers in various countries. [ 17–19 ] The selection of a suitable photocatalyst is a crucial determinant of photocatalytic degradation of antibiotics.…”
Section: Introductionmentioning
confidence: 99%